Benefit of postoperative radiotherapy for early tumors with single ipsilateral lymph node metastasis. (14th December 2019) - Weiss, Bernhard G.; Anczykowski, Mahalia Z.; Flach, Susanne; Spiegel, Jennifer L.; Kitz, Julia; Bertlich, Mattis; Canis, Martin; Jakob, Mark; Ihler, Friedrich
Abstract : Objectives/Hypothesis: Indication for postoperative radiotherapy in patients with locally circumscribed tumors (pT1–pT2) and a single ipsilateral lymph node metastasis (pN1) is debatable. The aim of this study was to evaluate the oncological long‐term outcome of patients with pT1‐pT2 pN1 squamous cell carcinoma (SCC) of the oral cavity, the oropharynx, and the hypopharynx without extracapsular spread (ECS) after a margin‐negative surgical resection, who either received or did not receive postoperative (chemo)radiotherapy. Study Design: Retrospective case series. Methods: The oncological outcome of patients with pT1‐pT2 pN1 SCC without ECS was evaluated retrospectively. All patients underwent primary tumor resection that included transoral laser microsurgery and neck dissection at an academic tertiary referral center. Results: Of 65 identified patients treated between 1986 and 2015 (18 oral cavity, 30 oropharynx, 17 hypopharynx), 21 (32%) received postoperative radiotherapy, and 44 (68%) were treated by surgery alone. The group of patients receiving postoperative treatment showed a significantly superior 5‐year disease‐specific (94.4% vs. 73.2%, P = .029) and recurrence‐free survival (85.2% vs. 43.2%, P = .002), as well as a higher local control rate (90.2% vs. 64.9%, P = .042). The overall survival was 71.4% vs. 62.6% ( P = .53). The mean follow‐up was 80.7 months. Conclusions: Patients with locally circumscribed carcinomas and a single ipsilateral ECS‐negative lymph node metastasis seem to benefit from postoperative radiotherapy. Level of Evidence: 4 Laryngoscope, 130:E530–E538, 2020